2014
DOI: 10.4103/0019-5413.125511
|View full text |Cite
|
Sign up to set email alerts
|

Microendoscopic lumbar discectomy: Technique and results of 188 cases

Abstract: Background:Discectomy performed open or with an operating microscope remains the standard surgical management. Tubular retractor system is being increasingly used. Potential benefits include less muscle and local damage, better cosmesis, decreased pain and operative time and faster recovery after surgery. We have evaluated the outcome of micro endoscopic discectomy (MED) utilizing tubular retractors in terms of safety and efficacy of the technique.Materials and Methods:188 consecutive patients who underwent su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
1
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 50 publications
3
40
1
4
Order By: Relevance
“…This surgical procedure has the following advantages: The field of operation is adjustable and anatomical structures such as nerves and the dural sac can be seen clearly through the endoscope. During the procedure, surgical instruments are less limited by the canals than with the METRx (Medtronic, Sofamor Danek, Memphis, TN, USA) system. The sleeves can be tilted at any angle according to the need to decompress the proximal, distal, lateral and contralateral spinal canals as well as the nerve root canals. The intervertebral disc and cartilaginous endplate structure can be scraped from all directions and the intervertebral space can be cleaned thoroughly by altering the angles of the sleeves. In contrast with open surgery, all required procedures, including segmental interlaminar fenestration decompression, discectomy, scraping of cartilaginous endplate and intervertebral bone grafting are performed with the aid of the endoscope; thus, the procedure can be performed with greater finesse and more safely.…”
Section: Discussionmentioning
confidence: 99%
“…This surgical procedure has the following advantages: The field of operation is adjustable and anatomical structures such as nerves and the dural sac can be seen clearly through the endoscope. During the procedure, surgical instruments are less limited by the canals than with the METRx (Medtronic, Sofamor Danek, Memphis, TN, USA) system. The sleeves can be tilted at any angle according to the need to decompress the proximal, distal, lateral and contralateral spinal canals as well as the nerve root canals. The intervertebral disc and cartilaginous endplate structure can be scraped from all directions and the intervertebral space can be cleaned thoroughly by altering the angles of the sleeves. In contrast with open surgery, all required procedures, including segmental interlaminar fenestration decompression, discectomy, scraping of cartilaginous endplate and intervertebral bone grafting are performed with the aid of the endoscope; thus, the procedure can be performed with greater finesse and more safely.…”
Section: Discussionmentioning
confidence: 99%
“…Garg et al, 13 reported one patient had a recurrence of disc herniation after 7 months. Kullarni et al, 23 reported a rate of recurrence 1.5%. Yadav et al, 50 reported recurrence occurred in 2 patients (0.5%).…”
Section: A B C Dmentioning
confidence: 99%
“…Most of the clinical series using this technique show low morbidity; which is usually related to dural tears. 17,23,24,31,38,39,46 In our series we had four patients of dural tears (2.6%); two of them (1.3%) developed CSF leaks; and one (0.6%) developed pseudomeningocele. We had one patient (0.6%) of partial nerve root injury (L5 root) that responded to pregabalin.…”
Section: A B C Dmentioning
confidence: 99%
See 2 more Smart Citations